(3HgLI GdeMGOK aj CMcGe LedI ef GdMhGOKs - (3eMeO Hf Ydj Hf eMeO Hf Ydj GdTHQGedSj GdeGdcj,J (B1021 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi dG jYRH TjA Yf Ydeg hdG jchf ai GdhLhO EdG HJbOjQg hMceg s
(3BNQgG (B:s
(3hdjcf gPG BNQ eG bUOfG EjQGOg ai gPg GdQSGdI hddg GdMeO hGdefI hUdi Gddg Ydi SjOfG eMeOq s
(3HgG fXGe GdJYbjHIs
(3ai BNQ GdQSGdI hQbJGf ajgeG(B: (3bGYOI jYQa efgG eYQaI GdMhGOK ai eSJbHd GdReGfs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B543 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B269s
Keywords: (3Gdadcs